PENGARUH HUMAN CAPITAL, STRUCTURAL CAPITAL, DAN CAPITAL EMPLOYED TERHADAP KINERJA KEUANGAN PERUSAHAAN (ROA) - Muhamad Emirza Tanjung (2017)
This study was conducted to examine the Influence Of Human Capital, Structural Capital, and Capital Employed Toward the Financial Performance of Companies (ROA) . This study uses banking companies listed in Indonesia Stock Exchange as a sample. Sampling technique using purposive sampling method. Selection of a sample of 43 banking companies listed in Indonesia Stock Exchange in 2015 resulted in 30 companies that are acceptable. Testing the hypothesis in this study using Multiple Linear Regression Analysis with EViews 9 and a significance level of 5 %. The results of the testing showed that: (1) human capital has a significant influence on the Financial Performance of Companies (ROA) with a significance level of 0.000 is smaller than the specified level α = 0.05. (2) The structural capital has no significant effect on the Financial Performance of Companies (ROA) because it has a significance level of 0.09 is greater than the specified level α = 0.05. (3) The capital employed has no significant effect on the Financial Performance of Companies (ROA) because it has a significance level of 0.0008 is greater than the specified level α = 0.05.